PEMBAHARUAN REGULASI PERKAWINAN ISLAM : ANALISIS POLITIK HUKUM DI INDONESIA - Army Putra Yudha; Fitria Agustin (CV. Denasya Smart Publisher, 2026)
This research provides a more in-depth explanation of the idea of reforming Islamic marriage law in the country. In general, the institution of marriage functions based on relationships among family members. These relationships may stem from kinship or be formed through the marriage itself. The importance of family relationships is closely linked to legal implications concerning children, parents, inheritance rights, custody, and guardianship. The aim of reforming Islamic marriage law implemented in this country is to adopt a modern approach in the field of marriage law. The primary sources of marriage law can essentially be derived through the method of istinbath (legal reasoning). Legal derivation may also employ the approaches of bayani (textual interpretation), ta’lili (causal reasoning), and istislahi (consideration of public interest). However, society understands marriage law through two types of sources: unwritten and written. Written legal sources include regulations derived from various laws and agreements. Meanwhile, unwritten legal sources develop and evolve within the context of social life in the community.